The Economic Benefits of Volunteering and Social Class - Robert M. Sauer; John Wilson; Noemi Mantovan (Institute of Labor Economics (IZA), 2019)
A theory that the economic benefits of volunteering are contingent on social class (as defined by similarities in labour market situation) is tested using seven waves of longitudinal data from the British Household Panel Study gathered between 1996 and 2008 and fixed-effects models. Volunteering has a positive effect on earnings, but it is confined to people in professional and managerial occupations. Employees in white and blue collar jobs do not benefit. The study suggests that inconsistent results from previous studies might be due to failure to consider occupational heterogeneity among volunteers.
Keywords: H4; J31; 330; volunteering; earnings; social class